2011
DOI: 10.1093/ecam/nen067
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss in Animals and Humans Treated with “Weighlevel”, a Combination of Four Medicinal Plants Used in Traditional Arabic and Islamic Medicine

Abstract: Weighlevel, a mixture of extract of four plants used in traditional Arabic and Islamic medicine as well as in European herbal medicine, was prepared and assessed for its safety and efficacy in weight loss. Leaves of Alchemilla vulgaris, Olea europaea and Mentha longifolia L., as well as seeds of Cuminum cyminum, were used. Cultured human fibroblasts treated with Weighlevel did not exhibit any sign of toxicity as evidenced by lactate dehydrogenase release. These results were confirmed in experimental studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…The herbal blend was also well tolerated and there were no safety concerns. This is in agreement with previous studies where the herbal blend was administered 3 times per day and produced weight loss of approximately 7% after 2 months of treatment and 10-13% weight loss after 3 months [10,11]. The weight loss observed with the once per day formulation was slightly lower than previously observed with the 3 times per day formulation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The herbal blend was also well tolerated and there were no safety concerns. This is in agreement with previous studies where the herbal blend was administered 3 times per day and produced weight loss of approximately 7% after 2 months of treatment and 10-13% weight loss after 3 months [10,11]. The weight loss observed with the once per day formulation was slightly lower than previously observed with the 3 times per day formulation.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism for weight loss with the herbal blend is hypothesized to be attributed to multiple effects including increased thermogenesis resulting in fat depletion, reduced blood glucose, and beneficial changes in digestion. Increased thermogenesis with the herbal blend has been demonstrated in Sprague-Dawley rats [11]. This is consistent with the reports of metabolic stimulation with extracts of Alchemilla vulgaris L. [16] and olive leaf [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Higher concentrations did not substantially add to such properties. These observations show a very high therapeutic index [2]. Also, [3] reported that LD 50 for A. vulgaris leaves is 17.3 g/Kg.…”
Section: Introductionmentioning
confidence: 69%
“…Increasing BAT activity is considered a new strategy for treating obesity. The clinical importance of BAT in combating obesity is noted because functional BAT has been demonstrated to be present in adults and an inverse correlation was observed between BAT activity and BMI [6,7]. Norepinephrine (NE) is considered an effective hormone in fat metabolism; it interacts with all three types of adrenergic receptors: b, a 2 and a 1 in the BAT [1].…”
Section: Introductionmentioning
confidence: 99%